Effects of acute aerobic exercise on emotional memory formation in individuals with methamphetamine use disorder: Encoding vs consolidation - Zhai, Xiaohui; Jin, Jianjing; Zhu, Ting; Cabral, Daniel A.R.; Wang, Dongshi; Chen, Jiachen; Zhao, Yiyang; Wang, Ke (Psychology of sport and exercise, 2025)
This study investigates the effects of acute aerobic exercise on the encoding and consolidation processes of emotional memory in individuals with methamphetamine use disorder (MUD). A within-subject cross-over design was utilized for both experiments. In Experiment 1, thirty-two participants engaged in 30 min of moderate-to-high intensity (70 %–80 % of predicted HRmax) aerobic exercise and a sedentary task before completing a learning task. Following a 50-min interval, participants completed a recognition task. In Experiment 2, thirty-six participants first completed the learning task, then engaged in a 30-min session of moderate-to-high intensity aerobic exercise or a sedentary task. After a 20-min interval, participants undertook the recognition task. The recognition task assessed participants’ accuracy in identifying old and new images, reaction times for recognition judgments, and confidence ratings. In Experiment 1, participants in the aerobic exercise condition exhibited significantly higher discrimination index d’ for neutral emotion images compared to those in the sedentary condition. Additionally, they demonstrated a significantly lower response bias index β for positive and neutral emotion images. Furthermore, participants in the aerobic exercise condition displayed significantly longer reaction times for both METH-related and negative images compared to those in the sedentary condition. In Experiment 2, no significant differences were observed in discrimination index d’, response bias index β, and reaction times between the two task conditions. This study reveals a significant impact of acute aerobic exercise on specific phases of emotional memory in individuals with MUD, particularly in enhancing encoding abilities. As a non-pharmacological intervention, exercise demonstrates the potential to alleviate addiction-related cognitive deficits and reduce the risk of relapse. The research further supports the prospect of integrating physical exercise into the treatment of substance use disorders, highlighting its critical role in promoting cognitive function recovery and overall therapeutic outcomes. •Acute aerobic exercise enhances emotional memory function in MUD.•Acute aerobic exercise facilitates encoding in MUD emotional memory.•Acute aerobic exercise heightens sensitivity to neutral emotions in MUD.•Acute exercise has no effect on the memory consolidation stage in MUD.•Acute exercise exhibits a temporary effect on episodic memory function.